Pre-Trial Settlement of Administrative Disputes in Lithuania: General Legal Characteristics - Paškevičienė, Laura (Teisė, 2018)
[only abstract in English; full article, abstract in Lithuanian]In Lithuania the extrajudicial settlement of administrative disputes is regulated by the main general laws, particularly, the Law on Administrative Proceedings, the Law on Public Administration and the Law of Administrative Dispute Commissions, which regulates the functioning of Lithuanian Administrative Disputes Commission as the quasi-court, having general competence of pre-trial administrative dispute resolution. Yet there are many special laws, which set different notions and norms of extrajudicial settlement of administrative disputes in separate fields of administrative law.In previous article having examined the substance and scientific insights on legal values, which relate to the pre-trial administrative dispute resolution, now the author continuously investigates the common normative legal background in the regulation of the pre-trial resolution of administrative disputes. This research is aimed at answering the main question, whether the norms of basic laws are sufficient to the formation of unanimous conception of institutional and functional system of pre-trial resolution of administrative disputes. Therefore, the article concentrates on the provisions of general legal regulation, which embed legal categories and criteria on the very description of the pre-trial administrative dispute resolution, and determine its position in the legal system, discerning from common administrative procedures. Also the author discusses the lack of common set and framework in this general regulation of the substantive procedural guaranties which ought to be adhered to the pre-trial dispute resolution, and finally – the effect of these general legal norms by vastly conferring the lawmaking and formation of the most legal characteristics of it to the same administrative authorities, having executive discretionary power.The author comes to conclusions, that in the provisions of general laws the legal category of the pre-trial administrative dispute resolution is described especially concisely, providing it should be established by the law. The legal description of administrative procedure autonomically is provided and regulated by the Law on Public Administration. But neither the Law on Administrative Proceedings, nor the Law on Administrative Dispute Commissions do give further qualitative criteria on the systematic establishment of the whole institutional and functional system of this kind of dispute resolution, clearly distinguishing it from common administrative procedures. This general regulation environment so far is not being elaborated in order to consolidate its legal provisions. Except the significant changes in the administrative dispute commissions regulation, broadening the provisions of the relevant law so that they now encompass the substantial material and procedural requisites and rules for its real functioning as the quasi-court, yet no respective essential alterations to regulatory arrangements of the pre-trial administrative dispute resolution in other institutions and the whole system have been made and are not expected in the near future. As the aspects of the possible independence and the level of judicial standards, transferable to the latter system still being not properly scientifically investigated, consequently this question is not raised in the initiatives of law making process. By the provisions of the discussed general legislation the established system of pre-trial administrative dispute resolution in administrative dispute commissions and other institutions in formal institutional and functional aspects is collateral. Yet general legislation does not ensure that in the use of essential material and procedural guaranties of the defense of persons’ rights the asymmetrical effect is avoided: the mentioned commissions are facultative institutions, whereas the regulation of the level and set of the material and procedural guaranties in special institutions (including compulsory ones), having a legal priority to the commissions, is vastly conferred to the specific laws of the particular area of public administration, relying the designing of the specific administrative dispute resolution on the legislative and administrative discretion. Using the latter, the administrative institutions can become not only the judge in its own case, but even “build the whole court”. Overall this does not sufficiently correspond with the nature and aims of the pre-trial resolution of administrative disputes, and constitutes an obstacle to systematize its legal regulation.
Keywords: none